1999
DOI: 10.1089/neu.1999.16.225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Hypothermia on Systemic and Internal Jugular Plasma IL-6 Levels After Traumatic Brain Injury in Humans

Abstract: Moderate hypothermia may reduce subsequent neuronal damage after traumatic brain injury. Interleukin (IL)-6 may have a role in the pathogenesis of traumatic neuronal damage or repair. Using the enzyme-linked immunological sorbent assay (ELISA), we serially measured IL-6 levels in plasma obtained from the radial artery (systemic) and internal jugular vein (regional) in 13 cerebral trauma patients who underwent hypothermia of 32-33 degrees C ranged from 4-9 days postinjury and 10 head-injured patients who were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(91 citation statements)
references
References 28 publications
4
84
1
1
Order By: Relevance
“…The 2 papers for which there was disagreement were considered for exclusion because some of the patients were pediatric. 27,34 As these studies reported individual patient data, we were able to exclude the pediatric data and we included only the adult data in our final analysis. During a later stage of analysis it was discovered that both of these studies were reporting the same set of patient results; therefore, only the most recent one was included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 papers for which there was disagreement were considered for exclusion because some of the patients were pediatric. 27,34 As these studies reported individual patient data, we were able to exclude the pediatric data and we included only the adult data in our final analysis. During a later stage of analysis it was discovered that both of these studies were reporting the same set of patient results; therefore, only the most recent one was included.…”
Section: Resultsmentioning
confidence: 99%
“…During a later stage of analysis it was discovered that both of these studies were reporting the same set of patient results; therefore, only the most recent one was included. 34 We identified 12 studies with 1327 participants that met our criteria for inclusion in this analysis ( Table 1). All 12 studies included mortality data and 10 also had data on functional outcome (dichotomized GOS).…”
Section: Resultsmentioning
confidence: 99%
“…Mild hypothermia has been shown to reduce proinflammatory cytokine levels such as IL-6 after different types of brain insults, including SAH [16,37,38]. As patients with therapeutic hypothermia need deep analgosedation, there might be no objective to administer NSAIDs for fever and pain management.…”
Section: Discussionmentioning
confidence: 99%
“…This inflammatory cascade causes additional neurotoxicity and apoptosis. There is strong evidence in experimental and clinical studies that hypothermia suppresses multiple aspects of this inflammatory reaction [30,47,48]. By the same token, mounting of the inflammatory response increases vascular permeability leading to vasogenic edema [49].…”
Section: Detrimental Effects Of Fevermentioning
confidence: 99%